Mathematical glimpse on the Y chromosome degeneration - Lobo, M. P. (Springer, 2006)
The Y chromosomes are genetically degenerate and do not recombine with their matching partners X. Non-recombination of XY pairs has been pointed out as the key factor for the degeneration of the Y chromosome. The aim here is to show that there is a mathematical asymmetry in sex chromosomes which leads to the degeneration of Y chromosomes even in the absence of XX and XY recombination. A model for sex-chromosome evolution in a stationary regime is proposed. The consequences of their asymmetry are analyzed and lead us to a couple of conclusions. First, Y chromosome degeneration shows up v 2 more often than X chromosome degeneration. Second, if nature prohibits female mortalities from beeing exactly 50%, then Y chromosome degeneration is inevitable.